A20 SNP rs77191406 may be related to secondary cancer for rheumatoid arthritis and systemic lupus erythematosus patients. Issue 4 (20th July 2016) - Zhu, Lihua; Zhou, Lingling; Wang, Liang; Li, Zhaoxia; Lu, Shuai; Yang, Lijian; Chen, Shaohua; Li, Bo; Wu, Xiuli; Zhou, Yi; Li, Yangqiu
Abstract: Aim: An increased risk for malignancy for rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) patients may be related to factors that play a critical role in the regulation of T‐cell activation. A20 is an important negative immunoregulatory factor that was found to be associated with lymphoma and the development of numerous solid tumors. Previous studies have implicated the A20 locus in RA susceptibility. In this study, we investigated polymorphisms in the A20 3′ UTR and explored whether there was an association between these polymorphisms and malignancy risk in autoimmune diseases. Methods: PCR and sequencing were used to identify A20 gene polymorphisms in peripheral blood mononuclear cells (PBMCs) from 99 RA cases, 37 SLE cases and 99 healthy individuals. Pearson's Chi square test was used for statistical analysis. Results: Only one SNP (rs77191406) and one new mutation (20132 A>G) in A20 gene were identified in RA and SLE patients and healthy individuals. Heterozygous rs77191406 was identified in just 1 of 99 RA patients and 2 of 37 SLE patients. More importantly, a RA patient who was heterozygous for rs77191406 developed colon cancer 10 years after the RA diagnosis. Similarly, two SLE patients carrying rs77191406 (heterozygous) had severe disease or developed bladder cancer 5 years after SLE diagnosis. Conclusions: These findings suggest that rs77191406 may be a prognostic marker for a high risk for rapid malignancy progression, poor survival and refractory disease and a new molecular marker associated with autoimmune diseases transforming into a secondary cancer.